Bandura”s Agent in Well-Being Imprvement and Poverty Eradication Among the Community in Kota Bharu, Malaysia - Razak, Ateerah Abdul; Md Nawi, Noor Hisham; Abd Latif, Siti Fathihah; Jamalludin, Nur Hafifah; Ahmad Kamal, Alia Nadhirah; Mohd Noor, Asma Lailee; Razak, Amanina Abdul (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The community in Kota Bharu, particularly the asnaf group, plays a crucial role in improving their quality of life. They possess the capacity to act as agents of change in reducing poverty within their community. This study aims to explore how these agents implement strategies to enhance economic and social well-being through community development projects, using Bandura’s theory of agency as a theoretical framework. A qualitative research approach was employed, utilizing in-depth interviews with participants to examine their business plans and monitor the outcomes of their entrepreneurial projects. Participants were selected through purposive sampling and were supervised over a period of time to assess their level of community development. The findings indicate that community members are able to apply Bandura’s agency framework in mitigating poverty within their communities. By adapting a development module based on the four components of Bandura’s agency, participants successfully improved their well-being and contributed to sustainable economic development. Furthermore, this study identifies several critical phases essential for ensuring the continuity of their efforts in overcoming future business challenges. Ultimately, the study aligns with the first United Nations Sustainable Development Goal (SDG 1) by contributing to poverty alleviation among marginalized populations.